No-tillage participatory quality index reflects the condition of soil management - Moraes de Cesare Barbosa, Graziela (2023)
Conservation agriculture is fundamental for improving agricultural sustainability. However, the quality of soil management in conservation agriculture systems is highly variable. The goal of this study was to verify whether a no-tillage participatory quality index (PQI) is associated with the physical, chemical, and microbiological attributes of soil. Thus, we sought to validate its use as an indicator of soil management quality. A survey was conducted to assess the agricultural practices of farmers from the western mesoregion of the state of Paraná, Brazil to evaluate the PQI. The quality of soil management for annual crops was related to the PQI, as evidenced by its association with soil physical, chemical, and microbiological attributes. These results confirmed the usefulness of the PQI methodology as a tool for assessing the quality of soil management, demonstrating its sensitivity to short-term changes in management practices. Consequently, this may allow for the monitoring of management quality and inferences about the beneficial effects of the implemented practices.